INTERNAL IMBALANCES AND GROWTH IN UKRAINE IN THE VIEW OF FISCAL AND MONETARY ISSUES - SHVETS, Serhii (Scientific journal «World of Finance», 2022)
Introduction. The frequent crises are a vital impediment to growth in Ukraine. One of the reasons is the accumulated imbalances, which objectively arise if ignoring the economic fundamentals in economic policy implementation. The purpose of the article is to study internal imbalances in Ukraine to determine the causes and consequences of economic slack given fiscal and monetary issues.Results. A critical observation of the Quantity Theory of Money approach in the balance between aggregate demand and supply made it possible to reconstruct the Ukrainian economy’s circular motion for the last ten years. The generation of the coincident and leading composite indices confirmed a difference to be at play between aggregate supply and demand. The parametric Early Warning System modeling results showed that an additional percentage of imbalances between aggregate demand and supply increased the likelihood of crises in Ukraine by 4%. The severe influence of the debt factor on macroeconomic dynamics made it possible to build up a quarterly econometric model by retranslating the exponential trend of the domestic public debt accumulation on GDP motion. The developed Dynamic Stochastic General Equilibrium model made it possible to reconstruct the economy’s prospect to move sustainable growth path, subject to implementing the golden rule of public finance. The fiscal multiplier effect offset the short-run crowding-out effect resulting from debt accumulation for financing public investment in favor of increased production in the long term. The significant parameter in this scenario is public investments efficiency, the increased level of which has to be one of the goals of the economic policy implementation.Conclusions. Fiscal-monetary interaction is crucial for counteracting macroeconomic imbalances and activating economic dynamics. Given the rise in public debt in Ukraine due to the Covid-19 pandemic, borrowing should be cautious while performing the fiscal investment expansion to stimulate growth.